Heterogeneity and Memory Effect in the Sluggish Dynamics of Vacancy Defects in Colloidal Disordered Crystals and Their Implications to High‐Entropy Alloys. Issue 36 (30th October 2022) - Chan, Chor‐Hoi; Huo, Qingxiao; Kumar, Anupam; Shi, Yunhong; Hong, Huihui; Du, Yitong; Ren, Simiao; Wong, Kin‐Ping; Yip, Cho‐Tung
Abstract: Vacancy dynamics of high‐density 2D colloidal crystals with a polydispersity in particle size are studied experimentally. Heterogeneity in vacancy dynamics is observed. Inert vacancies that hardly hop to other lattice sites and active vacancies that hop frequently between different lattice sites are found within the same samples. The vacancies show high probabilities of first hopping from one lattice site to another neighboring lattice site, then staying at the new site for some time, and later hopping back to the original site in the next hop. This back‐returning hop probability increases monotonically with the increase in packing fraction, up to 83%. This memory effect makes the active vacancies diffuse sluggishly or even get trapped in local regions. Strain‐induced vacancy motion on a distorted lattice is also observed. New glassy properties in the disordered crystals are discovered, including the dynamical heterogeneity, the presence of cooperative rearranging regions, memory effect, etc. Similarities between the colloidal disordered crystals and the high‐entropy alloys (HEAs) are also discussed. Molecular dynamics simulations further support the experimental observations. These results help to understand the microscopic origin of the sluggish dynamics in materials with ordered structures but in random energy landscapes, such as high‐entropy alloys. Abstract : Nonuniform distribution of particle size brings glassy properties to colloidal crystal systems. The vacancy dynamics of such disordered crystals are studied by experiments and molecular dynamics simulations. Heterogeneity and memory effect are observed in the sluggish vacancy dynamics. The results are further connected to the sluggish diffusion in high entropy alloys (HEAs).